Magnetic susceptibility of Griffiths like phase in poly- and nanocrystalline manganites La0.7Ca0.3MnO3. (31st October 2017) - Pękała, M; Pękała, K; Szydłowska, J; Drozd, V
Abstract: The Griffiths like phase is probed by the electron spin resonance and AC magnetic susceptibility in the poly- and nanocrystalline mixed valence manganites La0.7 Ca0.3 MnO3 . The novel method to analyze the Griffiths phase allows to determine a quickly decaying temperature variation of magnetic susceptibility of Griffiths phase in a whole interval between the Curie and Griffiths temperatures. A location of Griffiths phase is additionally confirmed by a nonvanishing out-of-phase component of magnetic susceptibility.